Character Values of Third Grade Slow Learner in Character Education at the Inclusive Elementary School - Pratama, Fiola Indah Putri; Kristiyanto, Agus; Widyastono, Herry (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The study aims to figure out the character values of 3rd grade slow learners’ students at the Inclusive Elementary School. Variables in this research were character values involving honesty, self-confidence, and discipline in learning. The sample consisted of 10 slow learner students of 3rd grade in seven Inclusive Elementary School. Data collection techniques used observations filled by classroom teachers. Data analysis techniques used the Guttmann scale. The score for the percentage of the slow learner's character value is 100% with low categorization. The solution was to provide character education in accordance with the characteristics of the slow learners. The implication was the slow learners got a character education model with method that paid attention to the characteristics of the child. This research is expected to be the basis for further research to be able to develop a character education model based on the BST method for the slow learners in inclusive elementary schools.